Bcc → hcp phase transition significantly enhancing the wear resistance of metastable refractory high-entropy alloy. (December 2022) - Yang, Wenqing; Luo, Jiasi; Fu, Hui; Cheung, Chi Fai; Ruan, Haihui; Yang, Xu-Sheng
Abstract: In this paper, cold rolling (55% reduction in thickness) plus different annealing temperatures were performed on the as-cast TiZrHfTa0.5 metastable refractory high-entropy alloy. The most bcc → hcp phase transition was found in the cold-rolled plus 870 °C-annealed specimens (average grain size of ∼ 30 μm), which exhibit the lowest coefficient of frictions (0.12–0.15) and wear rates ((4.08–9.68) × 10 −5  mm 3 /N m) under the dry-sliding loads of 16 N to 64 N at room temperature, relative to the as-cast and cold-rolled specimens with lower annealing temperatures. Atomic-scale observations revealed that composition-segregated bcc → hcp phase transition is further activated in the self-organized gradient worn subsurface, where the dual-phase structure with increased hcp phase fraction continues accommodating the repeated sliding-caused plasticity. Accordingly, two kinds of atomic movement mechanisms of bcc → hcp phase transition were dissected to be mainly executed by the cooperation of atom shuffling or/and partial dislocation dipoles gliding. Graphical abstract: Image, graphical abstract